2010
DOI: 10.1016/j.jhsa.2009.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Utility Analysis of Nonsurgical Management, Total Wrist Arthroplasty, and Total Wrist Arthrodesis in Rheumatoid Arthritis

Abstract: Purpose-Management of end stage rheumatoid wrist disease remains controversial. Total wrist fusion (TWF) provides reliable pain relief and stability and is the most commonly applied management strategy. Total wrist arthroplasty (TWA) is a motion-preserving alternative that is gaining popularity. The purpose of this study is to perform a cost-utility analysis comparing nonoperative management, TWA and TWF for the rheumatoid wrist Methods-A time trade-off utility survey was developed to investigate patient and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…This invites the opportunity to compare these two treatment options using the study of cost-utility. Cost-utility analysis considers costs, probabilities, and utilities of various health outcomes (health states) as a means to evaluate competing interventions [6]- [14].…”
Section: Both Sl and Lvos Have Variable Clinical Outcomes And Costs mentioning
confidence: 99%
“…This invites the opportunity to compare these two treatment options using the study of cost-utility. Cost-utility analysis considers costs, probabilities, and utilities of various health outcomes (health states) as a means to evaluate competing interventions [6]- [14].…”
Section: Both Sl and Lvos Have Variable Clinical Outcomes And Costs mentioning
confidence: 99%
“…Various economic models have been used in dentistry (7,12,13) and medicine (14,15) to evaluate the various treatment modalities. Cost-effectiveness analysis is one of the economic models used to assess the monetary value of a treatment.…”
mentioning
confidence: 99%
“…4 A cost-utility analysis of nonsurgical management, TWA, and arthrodesis for patients with rheumatoid wrist arthritis suggested that TWA and arthrodesis are both cost-effective procedures, with TWA having slightly greater cost compared with arthrodesis. 7 In a case series by Murphy et al, 8 there was no difference in patient-reported outcomes after TWA or arthrodesis, although patients with TWA showed a trend toward better performance of personal hygiene and fastening buttons. Although wrist arthrodesis is possible after failed wrist arthroplasty, it is technically challenging, and a high complication rate is reported.…”
Section: The Evidence Twamentioning
confidence: 97%